Targeted molecular imaging of TLR4 in hepatocellular carcinoma using zwitterionic near-infrared fluorophores - Ji, Yuanyuan; Wang, Zhidong; Bao, Kai; Park, G. Kate; Kang, Homan; Hu, Shuang; McDonald, Eric; Kim, Moon Suk; Kashiwagi, Satoshi; Choi, Hak Soo (Quantitative Imaging in Medicine and Surgery, 2019)
Background: Tumor-associated macrophages (TAMs) are one of the most abundant immune cell types in solid tumors and implicated in tumor progression. Toll-like receptor 4 (TLR4) is expressed in TAMs and plays a key role in immune surveillance and tumor progression. Therefore, molecular imaging of TLR4 has potential not only for detection of TAM-enriched progressing tumors, but also evaluation of TLR4 expression in tumor microenvironment. Methods: Here, we report that near-infrared (NIR) fluorescence imaging can provide a real-time imaging of a syngeneic model of murine hepatocellular carcinoma using targeted strategy against TLR4. We conjugated a zwitterionic NIR fluorophore ZW800-1C with minimal nonspecific tissue interactions to anti-TLR4 antibody and observed its targetability. The bioconjugates showed high affinity to murine macrophages in cell culture and in vivo. Results: Interestingly, we observed predominant NIR signals in the tumor site, which persisted for more than 48 h after single intravenous administration of the bioconjugate. Conclusions: This result suggests that TLR4 targeting combined with NIR fluorescence imaging is a useful tool for cancer imaging. This imaging strategy could be used to detect cancerous tissue with the increased TAM content and evaluate the status of TLR4 signaling in solid tumors, ultimately impacting on the diagnostic and prognostic imaging of human cancers.
Keywords: Hepatocellular carcinoma; NIR imaging; Toll-like receptor 4; Tumorassociated macrophages (TAMs); Zwitterionic fluorophore